Correlating the Interfacial Polar-Phase Structure to the Local Chemistry in Ferroelectric Polymer Nanocomposites by Combined Scanning Probe Microscopy - Liang, Jiajie; Wang, Shaojie; Luo, Zhen; Fu, Jing; Hu, Jun; He, Jinliang; Li, Qi (Nano-Micro Letters, 2022)
Ferroelectric polymer nanocomposites possess exceptional electric properties with respect to the two otherwise uniform phases, which is commonly attributed to the critical role of the matrix–particle interfacial region. However, the structure–property correlation of the interface remains unestablished, and thus, the design of ferroelectric polymer nanocomposite has largely relied on the trial-and-error method. Here, a strategy that combines multi-mode scanning probe microscopy-based electrical characterization and nano-infrared spectroscopy is developed to unveil the local structure–property correlation of the interface in ferroelectric polymer nanocomposites. The results show that the type of surface modifiers decorated on the nanoparticles can significantly influence the local polar-phase content and the piezoelectric effect of the polymer matrix surrounding the nanoparticles. The strongly coupled polar-phase content and piezoelectric effect measured directly in the interfacial region as well as the computed bonding energy suggest that the property enhancement originates from the formation of hydrogen bond between the surface modifiers and the ferroelectric polymer. It is also directly detected that the local domain size of the ferroelectric polymer can impact the energy level and distribution of charge traps in the interfacial region and eventually influence the local dielectric strength. Highlights: 1 A strategy that combines multi-mode scanning probe microscopy-based electrical characterization and nano-infrared spectroscopy is developed. 2 A series of samples with different coupling agents and nanoparticles are characterized to unveil the local structure-property correlation of the interface in ferroelectric polymer nanocomposites. 3 The formation of hydrogen bond between the surface modifiers and the ferroelectric polymer enhances the β-phase content and reduces the domain size of the interface, and hence promotes the local piezoelectric effect and breakdown strength.